UNDERSTANDING JAPANESE DEMOCRACY IN A POPULIST AGE. Issue 3 (27th May 2019) - Warren, David
Abstract : In this article, Sir David Warren, who was British Ambassador to Japan from 2008 to 2012, lays out the historical background to modern Japan, its political and economic structures (and international relationships); explores why we tend not to think of Japan as affected by the populism that we see in other Western democracies; and asks why Japan still presents itself as such a 'different' country.